Mixture Design for Minimizing Cement Content in Pavement Concrete. Issue 1 (January 2014) - Siddiqui, M. Sarwar; Rached, Marc; Fowler, David W.
Pavement concrete containing aggregates that do not meet ASTM C33 often experiences workability problems. One of the reasons is the lack of proper guidelines for proportioning concrete that contains aggregates with poor shape, texture, and grading. Commonly used methods, such as ACI 211, were developed for aggregates that meet ASTM C33; these methods are not adequate for optimizing mixtures containing aggregates such as manufactured sands. This paper presents a simple mixture proportioning method for designing pavement concrete with low slump. The proposed method has the potential to minimize the cement content of paving mixtures with any available source or combination of aggregate without affecting performance. Several combinations of aggregates were tested and the results for slump, compressive strength, and modulus of elasticity are presented in this paper.